Humor in Deaf Culture - Radić Šestić, Marina; Šešum, Mia; Radovanović, Vesna; Ivanović, Maja (Specijalna edukacija i rehabilitacija, 2020)
Visual experience and visually based linguistic communication are two key aspects of Deaf culture. When incorporated into humor, its members share specific experience. This paper aims to review the available literature in order to determine whether the humor of the deaf differs from the humor of hearing population, and if so, how and to what extent. Richness of humor in deaf culture is reflected in the variety, creativity and complexity of expression, using different strategies. The first strategy is reflected in using sign language to tell stories which are witty and have a comic point. The second strategy consists of  imitating animals and humans (caricature). The third strategy refers to using sign language to create  invented, fanciful, absurd images that do not exist in reality. The fourth type of humor is in sign language which is difficult to translate. It is a type of humor that has to be seen, and where people enjoy its visual logic and the redundancy of silent film images. The attempt to translate the humorous content of Deaf culture and share it with the hearing population should be seen not only as interlingual, but also as intercultural operation. Hence the lack of understanding between these two social groups.
Keywords: humor, Deaf culture, hearing population